1994
DOI: 10.1002/chin.199432011
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Structure and Synthesis of Lutetium Germanate Lu6Ge4O17.

Abstract: Structure and Synthesis of Lutetium Germanate Lu6Ge4O17.-Crystals of novel compound Lu6Ge4O17 are grown using the method of spontaneous crystallization from melts of Lu2O3, GeO2, B2O3 and PbO as flux. The germanate crystallizes in the monoclinic system (space group P2/c, Z = 2). X-ray studies indicate the presence of two kinds of anionic groupings, slightly distorted tetrahedral GeO4-4-anions and Ge2O6-7-anions of angular structure. Three crystallographically independent Lu-atoms with octahedral oxygen coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…From the similarity of powder diffraction patterns it was concluded that these crystals show a very similar or even isomorphic structure, but, a crystal structure determination is reported for the title compound LaBO 2 MoO 4 , only [32]. Besides the evidence of their existence and the crystal structure information, no further data about the series LnBO 2 M O 4 are given in literature.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…From the similarity of powder diffraction patterns it was concluded that these crystals show a very similar or even isomorphic structure, but, a crystal structure determination is reported for the title compound LaBO 2 MoO 4 , only [32]. Besides the evidence of their existence and the crystal structure information, no further data about the series LnBO 2 M O 4 are given in literature.…”
Section: Introductionmentioning
confidence: 82%
“…The origin of this phenomenon is subject to further studies. Typically, our crystals of LaBO • , that we determined from refined powder X-ray diffraction data (note that in [32] a different set- [32], see Fig. 1.…”
Section: Crystallography and Linear Opticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the refractive indices offer the possibility for phase-matched generation of the second harmonic with type I phase-matching for wavelengths above ≈ 0.89 µm and additionally phase-matching type II for wavelengths above ≈ 1.28 µm of the fundamental wave (see Fig. 1), and the crystal structure is reported to have a pronounced polar symmetry with space group P2 1 [13], only a very weak SHG was detected in our previous investigations [9]. From temperature-dependent polarization microscopy no hints to any structural instability could be found in the temperature region between 100 K and 1273 K, especially, no hints to twin formation was found in transmitted polarized light.…”
Section: Crystallography and Crystal Growthmentioning
confidence: 99%